Animal Cancer Research - Sahoo, Aditya P.; Somvanshi, R.; Sonal, Sonal; Kumar, G. Ravi; Kumar, Pawan; Tiwari, Ashok K. (Indian Farming, 2015)
In spite of all the advances made recently in human cancertherapeutics, adequate therapeutic approaches are still lacking formanaging the animal cancer patients. Therefore, research initiated by IVRI in the field of animal cancer vaccines, gene therapy and diagnostics may provide a ray of hope for the future.